PENGEMBANGAN APLIKASI SURAT MENYURAT DARI KECAMATAN MEKAR BARU KE DESA BERBASIS MOBILE - Noviyanti, Ayu; Aryono, Gagah Dwiki Putra; Auliana, Sigit (Politeknik Bisnis Indonesia, 2025)
The objective of this research is to address issues with correspondence administration in Mekar Baru Subdistrict, which still uses physical documents, causing problems such as lost or damaged letters and difficulties in monitoring letter disposition in real time. The SiMekar mobile application was created using the Flutter framework and the Waterfall software development method as a solution. The main features of this application include incoming and outgoing letter management, digital disposition, real-time notifications, and role-based user authentication and authorisation. Interviews, observations, and documentation of administrative processes were used to collect data. The results of observations and testing show that all application functions operate in accordance with user needs, and the digitalisation of letter-writing processes using this application can enhance the speed, accuracy, efficiency, and transparency of letter management in sub-district governments. Therefore, the SiMekar application is a useful digital solution to support public administration transformation through the use of information technology.